Prevalence, risk factors, and adverse perinatal outcomes in Chinese women with preeclampsia: a large retrospective cohort study - Lin Chai; Shuai Li; Binbin Yin; Xiaojun Zhu; Bo Zhu; Kaiqi Wu (Journal of Health, Population and Nutrition)
Abstract Background Preeclampsia (PE) is the primary cause of maternal and neonatal morbidity and mortality. However, comprehensive studies on the related risk factors with PE and its effects on adverse perinatal outcomes are limited. This study aimed to evaluate the prevalence, risk factors, and adverse perinatal outcomes in Chinese women with preeclampsia. Methods We conducted a retrospective cohort study from January 1, 2018, to December 31, 2019, which enrolled 38,496 women without preeclampsia (non-PE) and 1130 women with PE. Univariate and multivariate logistic regression models were used to determine the risk factors and adverse perinatal outcomes of PE. Results Multivariate logistic regression models showed that maternal age > 35 years, pp-BMI overweight/obesity, excessive gestational weight gain, multiparity, twin pregnancy, IVF, cesarean section history, times of abortion history ≥ 2, GDM, and ICP were significantly associated with the risk of PE (all P < 0.05). Women with PE in singleton pregnancies were associated with an increased risk of maternal outcomes of cesarean section, and preterm birth, and a higher risk of neonatal outcomes of stillbirth, low birth weight, fetal distress, neonatal asphyxia, and neonatal unit admission, which were also observed in women with PE in twin pregnancies, except for stillbirth and neonatal asphyxia. Conclusion This study identified the risk factors and associated adverse perinatal outcomes of PE, which providing comprehensive evidence for clinicians to manage women at risk of PE.